Blockade of the NLRP3 inflammasome improves metabolic health and lifespan in obese mice - Cañadas-Lozano, Diego (GeroScience, 2020)
Aging is the major risk factor for many metabolic chronic diseases. Several metabolic pathways suffer a progressive impairment during aging including body composition and insulin resistance which are associated to autophagy dysfunction and increased inflammation. Many of these alterations are aggravated by non-healthy lifestyle such as obesity and hypercaloric diet which have been shown to accelerate aging. Here, we show that the deleterious effect of hypercaloric diets is reverted by the NLRP3 inflammasome inhibition. NLRP3 deficiency extends mean lifespan of adult mice fed a high-fat diet. This lifespan extension is accompanied by metabolic health benefits including reduced liver steatosis and cardiac damage, improved glucose and lipid metabolism, and improved protein expression profiles of SIRT-1, mTOR, autophagic flux, and apoptosis. These findings suggest that the suppression of NLRP3 prevented many age-associated changes in metabolism impaired by the effect of hypercaloric diets. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11357-019-00151-6) contains supplementary material, which is available to authorized users.